Utilization of Magrove Muds In the Kuala Langsa as A Source of Electricity - Meutia, Eva; Nurbaiti, Upik; Yulianto, Agus (Faculty of Science and Education, UIN Walisongo Semarang, 2025)
The economic potential of mangroves can be a provider of economic resources, preserving the ecological environment and providing environmental services. Mangrove soil in Kuala Langsa is important to study as the potential for carbon sequestration in the form of biomass, the social potential of the community in supporting the development of efforts. The purpose of this study was to determine how much electricity was generated by the Kuala Langsa mangrove mud soil and how the effect of variations in electrode material on the electricity produced by the Langsa mangrove mud soil. The method used is to use a series of voltaic cells. The results of this study obtained data that mangrove mud soil can be used as alternative energy by using variations of Cu-Zn and Cu-Al electrode pairs with a mangrove mud mass of 350 ml, at Cu-Zn electrode pairs the largest electric power obtained is 0,8736 J/s. with the lamp on while the Cu-Al electrode pair obtained an electric power of 0,1794 J/s with the lamp not lit